Role of Foreign Tourist Arrivals (FTAs) from Bangladesh in Indian Tourism Development: A Segment-wise Analysis - Karim, Rajaul (Turizam, 2020)
Bangladesh being a neighboring country of India plays a crucial role in bringing millions of tourists every year. Bangladesh is the largest tourist generating market for India in which the India-Bangladesh relation is a key factor for this foreign tourist arrivals(FTAs) and tourism development. The main objective of this paper is to find out the trend of Bangladeshi foreign tourist arrivals in India from 2018 to 2025 with respect to observed values of foreign tourist arrivals during previous years, analysis of segment-wise growth rate of Bangladeshi tourist arrivals according to purpose of travel and to make some policy prescriptions. The research is based on secondary data by applying descriptive statistics considering the published reports of the Indian Government from the Ministry of Tourism. The findings of the present research paper show that the trend and growth rate of FTAs are rising steadily as well as the importance of Bangladeshi tourist arrivals in developing certain tourism segments of India that are lacking behind and have some potential for further expansion. Proper attention to these segments is expected to make a positive contribution towards tourism development in particular and economic development in general of India.
Keywords: Foreign Tourist Arrivals (FTAs),Bangladeshi Tourist,Tourism Potentiality,Indian Tourism Development.